Smart healthcare applications and services developments and practices - Röcker, Carsten 1975-; Ziefle, Martina Cornelia 1962- (Premier reference source, 2011)
"This book provides an in-depth introduction into medical, social, psychological, and technical aspects of smart healthcare applications as well as their consequences for the design, use and acceptance of future systems" - Provided by publisher